Beneficial Effects of Fingolimod on Social Interaction, CNS and Peripheral Immune Response in the BTBR Mouse Model of Autism. (21st May 2020) - De Simone, Roberta; Butera, Alessia; Armida, Monica; Pezzola, Antonella; Boirivant, Monica; Potenza, Rosa Luisa; Ricceri, Laura
Highlights: Fingolimod (FTY720) improves social responsiveness in BTBR male mice, a mouse model of autism spectrum disorder. FTY720 normalizes hippocampal BDNF mRNA levels in BTBR male mice. FTY720 reduces central and peripheral inflammatory state and normalizes gut innate immune-response in BTBR male mice. Abstract: Autism Spectrum Disorders (ASD) are neurodevelopmental disorders characterized by social communication deficits and repetitive/stereotyped behaviours. We evaluated the effects of a chronic treatment with the immunomodulator drug Fingolimod (FTY720 – a non-selective Sphingosine 1-Phosphate Receptor ligand) in an ASD model, the BTBR T + tf/J (BTBR) mouse strain. In adult BTBR males, chronic FTY720 treatment (4 weeks) increased social and vocal response during a male–female interaction and hippocampal expression of BDNF and Neuregulin 1, two trophic factors reduced in BTBR when compared to control C57 mice. FTY720 also re-established the expression of IL-1β and MnSOD in the hippocampus, whereas it did not modify IL-6 mRNA content. In addition to its central effect, FTY720 modulated the activation state of peripheral macrophages in the BTBR model, both in basal conditions and after stimulation with an immune challenge. Furthermore, IL-6 mRNA colonic content of BTBR mice, reduced when compared with C57 mice, was normalized by chronic treatment with FTY720. Our study, while indicating FTY720 as a tool to attenuate relevant alterations of the BTBR neurobehavioural phenotype, emphasizes the importance of gut mucosal immune evaluation as an additional target that deserve to be investigated in preclinical studies of anti-inflammatory therapeutic approaches in ASD.